Economic feasibility of bifacial silicon solar cells. (14th January 2016) - Fertig, Fabian; Nold, Sebastian; Wöhrle, Nico; Greulich, Johannes; Hädrich, Ingrid; Krauß, Karin; Mittag, Max; Biro, Daniel; Rein, Stefan; Preu, Ralf
Abstract: Bifacial solar cells and modules are a promising approach to increase the energy output of photovoltaic systems, and therefore decrease levelized cost of electricity (LCOE). This work discusses the bifacial silicon solar cell concepts PERT (passivated emitter, rear totally diffused) and BOSCO (both sides collecting and contacted) in terms of expected module cost and LCOE based on in‐depth numerical device simulation and advanced cost modelling. As references, Al‐BSF (aluminium back‐surface field) and PERC (passivated emitter and rear) cells with local rear‐side contacts are considered. In order to exploit their bifacial potential, PERT structures (representing cells with single‐sided emitter) are shown to require bulk diffusion lengths of more than three times the cell thickness. For the BOSCO concept (representing cells with double‐sided emitter), diffusion lengths of half the cell thickness are sufficient to leverage its bifacial potential. In terms of nominal LCOE, BOSCO cells are shown to be cost‐competitive under monofacial operation compared with an 18% efficient (≙ p MPP  = 18 mW/cm 2 ) multicrystalline silicon (mc‐Si) Al‐BSF cell and a 19% mc‐Si PERC cell for maximum output power densities of p MPP  ≥ 17.3 mW/cm 2 and p MPP  ≥ 18.1 mW/cm 2, respectively. These values assume the use of $10/kg silicon feedstock for the BOSCO and $20/kg for the Al‐BSF and PERC cells. For the PERT cell, corresponding values are p MPP  ≥ 21.7 mW/cm 2 and p MPP  ≥ 22.7 mW/cm 2, respectively, assuming the current price offset (≈50%, at the time of October 2014) of n ‐type Czochralski‐grown silicon (Cz‐Si) compared with mc‐Si wafers. The material price offset of n ‐type to p ‐type Cz‐Si wafers (≈15%, October 2014) currently accounts for approximately 1 mW/cm 2, which correlates to a conversion efficiency difference of 1%abs for monofacial illumination with 1 sun. From p ‐type mc‐Si to p ‐type Cz‐Si (≈30% wafer price offset, October 2014), this offset is approximately 2.5 mW/cm 2 for a PERT cell. When utilizing bifacial operation, these required maximum output power densities can be transformed into required minimum rear‐side illumination intensities for arbitrary front‐side efficiencies η front by means of the performed numerical simulations. For a BOSCO cell with η front  = 18%, minimum rear‐side illumination intensities of ≤ 0.02 suns are required to match a 19% PERC cell in terms of nominal LCOE. For an n ‐type Cz‐Si PERT cell with η front  = 21%, corresponding values are ≤ 0.11 suns with 0.05 suns being the n ‐type to p ‐type material price offset. This work strongly motivates the use of bifacial concepts to generate lowest LCOE. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This work discusses the bifacial silicon solar cell concepts passivated emitter, rear totally diffused (PERT) and both sides collecting and contacted (BOSCO) in terms of expected module cost and levelized cost of electricity (LCOE) based on in‐depth numerical device simulation and advanced cost modelling. As references, aluminium back‐surface field (Al‐BSF) and passivated emitter and rear cells (PERC) cells with local rear‐side contacts are considered. Required maximum output power densities and rear‐side illumination intensities are determined, for PERT and BOSCO to be cost‐competitive compared with an 18% mc‐Si Al‐BSF and a 19% mc‐Si PERC cell. This work strongly motivates the use of bifacial concepts to generate lowest LCOE.